Biomolecule–nanoparticle interactions: Elucidation of the thermodynamics by isothermal titration calorimetry - Huang, Rixiang; Lau, Boris L.T. (Biochimica et biophysica acta, 2016)
Nanomaterials (NMs) are often exposed to a broad range of biomolecules of different abundances. Biomolecule sorption driven by various interfacial forces determines the surface structure and composition of NMs, subsequently governs their functionality and the reactivity of the adsorbed biomolecules. Isothermal titration calorimetry (ITC) is a nondestructive technique that quantifies thermodynamic parameters through in-situ measurement of the heat absorption or release associated with an interaction. This review highlights the recent applications of ITC in understanding the thermodynamics of interactions between various nanoparticles (NPs) and biomolecules. Different aspects of a typical ITC experiment that are crucial for obtaining accurate and meaningful data, as well as the strengths, weaknesses, and challenges of ITC applications to NP research were discussed. ITC reveals the driving forces behind biomolecule–NP interactions and the effects of the physicochemical properties of both NPs and biomolecules by quantifying the crucial thermodynamics parameters (e.g., binding stoichiometry, ΔH, ΔS, and ΔG). Complimentary techniques would strengthen the interpretation of ITC results for a more holistic understanding of biomolecule–NP interactions. The thermodynamic information revealed by ITC and its complimentary characterizations is important for understanding biomolecule–NP interactions that are fundamental to the biomedical and environmental applications of NMs and their toxicological effects. This article is part of a Special Issue entitled Microcalorimetry in the BioSciences — Principles and Applications, edited by Fadi Bou-Abdallah. •ITC is a nondestructive technique that measures in situ the heat changes associated with NP-biomolecule interactions.•Careful planning/preparation and accurate concentration determination are critical for a successful ITC experiment.•Thermodynamic parameters derived by ITC help reveal the mechanisms behind NP-biomolecule interaction.•ITC enables a quantitative evaluation on the effects of the properties of NP and biomolecule on their interaction.•Complimentary tools are needed to cross-validate and accurately interpret ITC results and obtain more interaction details.